Characterization of Xanthan gum-based hydrogel with Fe3+ ions coordination and its reversible sol-gel conversion. (1st January 2019) - Kang, Mengmeng; Oderinde, Olayinka; Liu, Shunli; Huang, Qianqian; Ma, Wenjing; Yao, Fang; Fu, Guodong
Highlights: Hydrogels based on Xanthan gum coordinated in situ with iron ions were fabricated under ambient temperature. The Xanthan gum-based hydrogel could achieve sol-gel conversion by UV irradiation in the presence of sodium lactate. The viscosity changing and viscoelastic property was investigated to studied the sol-gel conversion. Abstract: Since redox-responsive hydrogels have a wide range of applications especially in biochemistry, such as drug release and biosensors, a kind of redox-responsive hydrogel was fabricated based on iron which has two stable oxidation states, while xanthan gum (XG) was selected as a matrix. In this work, characterization of XG-based hydrogel with Fe 3+ ions coordination and its reversible sol-gel conversion property were studied. Xanthan gum solutions with different concentrations were coordinated in situ with constant trivalent iron ions concentration to form hydrogels under ambient temperature. The chemical features of XG-based hydrogels were characterized by Fourier transform infrared spectroscopy (FT-IR) and ultraviolet visible light spectrum (UV–vis), while scanning electron microscope (SEM) was used to observed the morphologies of XG-based hydrogels cross-sections. In addition, the mechanical properties, thermal stability and swelling behavior of xanthan gum hydrogels were also investigated, respectively. The results showed that xanthan gum hydrogels possessed relatively uniform layered structure, in addition to possessing enhanced mechanical strength and excellent swelling behavior. Furthermore, the sol-gel conversion of XG-based hydrogel could be realized by UV light in the presence of sodium lactate. The process of changes in viscosity was studied. The result indicated that the XG-based hydrogel could be recycled and these characteristic studies may be of reference for future use of xanthan gum hydrogels in the field of biomedical materials or sensors.